Association between fluoride exposure and the risk of serum CK and CK-MB elevation in adults: a cross-sectional study in China - Junhua Wu; Ming Qin; Yue Gao; Yang Liu; Xiaona Liu; Yuting Jiang; Yanmei Yang; Yanhui Gao (Frontiers in Public Health)
BackgroundThis study aimed to investigate the relationship between urinary fluoride concentration and myocardial disease.MethodsThis is a cross-sectional study that was conducted in three villages in Wenshui County, Shanxi Province. A total of 737 villagers were included in this analysis. Urinary fluoride was detected using a fluoride-ion selective electrode. Myocardial enzymes were detected using an automatic biochemical analyzer. Myocardial ischemia and arrhythmia were diagnosed using 12-lead electrocardiogram.ResultsThe median level of urinary fluoride concentration was 1.32 mg/L. Urinary fluoride was associated with serum creatine kinase (CK) elevation (odds ratio [OR] = 1.39 [95% confidence interval (CI)]: 1.09–1.78) and CK isoenzyme (CK-MB) elevation (OR = 1.49 [95% CI: 1.12–1.97]). Stratified analysis revealed that urinary fluoride concentration was associated with CK elevation in villagers under the age of 60 years (OR = 1.80 [95% CI: 1.26–2.59]). This study found that there was a positive association between urinary fluoride concentration and the risk of CK-MB elevation in participants under the age of 60 years(OR = 2.18 [95% CI: 1.39–3.42]), those who were of female gender (OR = 1.53 [95% CI: 1.07–2.19]), those who were overweight/obese (OR = 1.96 [95% CI: 1.28–2.99]), those who had central obesity (OR = 1.59 [95% CI: 1.12–2.25]), consumed alcohol (OR = 1.49 [95% CI: 1.09–2.05]), and smoked (OR = 1.50 [95% CI: 1.10–2.04]).ConclusionOur study suggests that fluoride exposure is associated with the risk of serum CK and CK-MB elevation; however, it is not associated with myocardial ischemia, arrhythmia, serum lactate dehydrogenase (LDH), serum alpha-hydroxybutyrate dehydrogenase (α-HBD), or serum aspartate aminotransferase (AST). Further investigations are needed to substantiate our findings and explore the potential underlying mechanisms.